Combining the switched-beam and beam-steering capabilities in a 2-D phased array antenna system - Tsai, Yi-Che; Chen, Yin-Bing; Hwang, Ruey-Bing (My University, 2016)
This paper presents the development, fabrication, and measurement of a novel beam-forming system consisting of 16 subarray antennas, each containing four aperture-coupled patch antennas, and the application of this system in smart wireless communication systems. The beam patterns of each of the subarray antennas can be switched toward one of nine zones over a half space by adjusting the specific phase delay angles among the four antenna elements. Furthermore, when all subarrays are pointed at the same zone, slightly continuous beam steering in around 1 degrees increments can be achieved by dynamically altering the progressive phase delay angle among the subarrays. Phase angle calibration was implemented by coupling each transmitter output and down converter into the in-phase/quadrature baseband to calculate the correction factor to the weight. In addition, to validate the proposed concepts and the fabricated 2-D phased array antenna system, this study measured the far-field radiation patterns of the aperture-coupled patch array integrated with feeding networks and a phase-calibration system to carefully verify its spatially switched-beam and beam-steering characteristics at a center frequency of 2.4GHz which can cover the industrial, scientific, and medical band and some long-term evolution applications. In addition, measured results were compared with calculated results, and agreement between them was observed.
Keywords: aperture-coupled patch antennas; beam-forming system; beam steering; switched beam